2015
DOI: 10.1007/s10661-015-4961-0
|View full text |Cite
|
Sign up to set email alerts
|

Imposex in the dogwhelk (Nucella lapillus): 22-year monitoring around England and Wales

Abstract: Six imposex surveys in the dogwhelk (Nucella lapillus) have been conducted over the past two decades to assess legislation effectiveness controlling the use of tri-butyl tin (TBT) by the maritime shipping industry. This study firstly analysed the results of the 2014 survey and secondly carried out a trend assessment of the same 88 sampled sites between 1997 and 2014 of which 65 showed statistically significant reductions. To highlight the magnitude of change, the Vas Deferens Sequence stages (VDS) of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Despite some legacy pollution issues due to contaminated sediments, populations in the southwest of England had largely recovered to low levels of imposex a decade later, by around the year 2000. A re-survey in 2016 confirmed this, with imposex being undetectable in the previously routinely monitored populations (see also Langston et al, 2015;Matthiessen, 2013;Nicolaus and Barry, 2015;Wilson et al, 2015).…”
Section: Tributyltin Pollutionmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite some legacy pollution issues due to contaminated sediments, populations in the southwest of England had largely recovered to low levels of imposex a decade later, by around the year 2000. A re-survey in 2016 confirmed this, with imposex being undetectable in the previously routinely monitored populations (see also Langston et al, 2015;Matthiessen, 2013;Nicolaus and Barry, 2015;Wilson et al, 2015).…”
Section: Tributyltin Pollutionmentioning
confidence: 67%
“…The scientific community also has an excellent record of prompting governments to act. Success stories include identification of the pernicious influence of some pesticides (Carson, 1962), dealing with sewage pollution in fresh and coastal waters (EU Water Framework Directive), and identifying and dealing with TBT pollution (Langston et al, 2015;Nicolaus and Barry, 2015). Emerging pollution issues are sometimes identified by scientists and then taken up by campaigning organisations in civil society.…”
Section: Pollution In the Context Of Other Impactsmentioning
confidence: 99%
“…The X and Y axes represent the longitude Northern length (NL) and the latitude Eastern length (EL), respectively. Langston et al, 2015;Nicolaus and Barry, 2015;Wilson et al, 2015;HELCOM, 2018;Schøyen et al, 2018). The unequal recovery in time is not surprising since the 1989 TBT restrictions on small ships had mainly a local impact in predominantly recreational and small ships areas.…”
Section: Tbt Levels In the Southern North Seamentioning
confidence: 99%
“…This paper assesses different aspects of TBT pollution in C. crangon in its main distribution range, the southern North Sea and does not focus on an overall review on TBT data and effects in the marine environment, as the TBT levels vary by a high factor in different locations. For comprehensive reviews, we refer to, among other (Evans et al, 1996;Fent, 1996;Champ, 2000;Birchenough et al, 2002;Stronckhorst and van Hattum, 2003;Antizar-Ladislao, 2008;Morton, 2009;Oliveira et al, 2009;Rodríguez et al, 2009;Sousa et al, 2009;Bengtsson and Wernersson, 2012;Sunday et al, 2012;Matthiessen, 2013;Wetzel et al, 2013;OSPAR, 2014;Langston et al, 2015;Nicolaus and Barry, 2015;Wilson et al, 2015;Schøyen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The degree of imposex reversibility depends on the snail species. Some studies have shown that the imposex response in Nucella lapillus is largely irreversible for individuals (Bryan et al ); however, snail populations have recovered worldwide after the reduction in use of TBT as an antifoulant (Birchenough et al ; Matthiessen ; Nicolaus and Barry ). Similarly, Birch et al () found a correlation between the recovery of rock oyster ( Saccostrea glomerata ) populations and the reduction of TBT in estuaries with high densities of boat moorage.…”
Section: Introductionmentioning
confidence: 99%